(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Patellar fractures are relatively uncommon, accounting for about 1% of all skeletal injuries and transverse fracture pattern is the most common pattern. Early and appropriate management is essential to restore knee function and minimize long-term complications. This study aimed to describe the profile of patients with closed transverse patellar fractures managed in a tertiary level teaching hospital in Bangladesh. Materials and methods: The prospective study of 20 closed transverse patellar fracture cases was conducted at the Department of Orthopaedics of Chittagong Medical College Hospital from January 2019 to December 2020. Patients were managed by open reduction and internal fixation with Tension Band Wiring (TBW) using parallel Cannulated compression screws. Results: The mean age of the patients was 38.91 ±12.01 years, ranging from 19 to 60 years. Most (80%) of the patients were male and farming was the predominant occupation (30%). Thirteen patients (65%) presented with right-sided fractures and the majority of the injuries were caused by either motor-vehicle accidents (45%) or accidental falls (45%). After six months of injury, 15 (75%) and 5 (25%) patients had full extension and 120 degree and 90-120 degree Range of Motion (ROM) respectively. The main complication was knee stiffness, observed in 10% of patients. Conclusion: Transverse patellar fractures are most commonly seen in young adult males and result from direct trauma to the knee. Six-month outcomes were favourable with appropriate management. JCMCTA 2025 ; 36 (1) : 10-13